Mobile Learning Media Development on Kampung KB Management Training Material for Family Planning Field Worker in East Java - Widi Asih Nurhajati (Proceedings of The ICECRS, 2019)
In facing the 4.0. Industrial revolution era, the usage of technology becomes a prominent needs to enhance the opportunity of learning for Family Planning Field Worker (PKB) in East Java. Therefore a media should be developed to transfer the knowledge of learning material, especially for Kampung KB material as the priority program of Indonesian Population and Family Planning Board (BKKBN) towards all PKB in East Java. The study aims to determine the appropriateness of mobile learning media to develop the learning outcomes of East Java’s PKB in mastering Kampung KB management training material. It uses research development method by Borg and Gall (2003). The results indicates that it is proper since the value of the individual test is 93.94%, 88.64% in the small group test, and 87.87% in the large group test. The effectiveness of the media is proven by the average value of the experimental class posttest of = 77.17 while the pretest is only 46.33. The posttest significance value of the experimental class was 0.181> 0.05, so that there were differences in learning outcomes between before and after learning using mobile learning media in the Kampong Management training material